Effect of membrane moiety and magnesium ions on the inhibition of matrix-induced alkaline phosphatase by zinc ions - Clancaglini, Pletro; Plzauro, João M. [UNESP]; Curti, Carlos; Tedesco, Antonio C.; Leone, Francisco A. (Elsevier, 1990)
1. 1. The inhibition of matrix-induced alkaline phosphatase by zinc ions is due to the displacement of magnesium ions from its binding site. 2. 2. Binding of magnesium ions to alkaline phosphatase induces conformational changes which activate the enzyme. 3. 3. Binding of zinc ions to alkaline phosphatase induces conformational changes which impair the catalytic action of the enzyme. 4. 4. The inhibition of the enzyme by zinc ions is affected by membrane environment and magnesium ions. © 1990.